An Integrated SCOR–AHP Approach for Halal Traceability Supply Chain Management in the Food Industry - Yeni Hendriyani; Iwan Setiawan; Ija Suntana; Mohamad Anton Athoillah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2026)
The rapid growth of the global halal food market has intensified the need for effective halal traceability across increasingly complex supply chains. Despite mandatory halal certification policies in Indonesia, maintaining halal integrity throughout the entire supply chain remains a significant challenge, particularly in the food service sector. This study aims to identify priority criteria for halal traceability supply chain management and to develop an integrated strategic framework by combining the Supply Chain Operation Reference (SCOR) model version 14.0 with the Analytic Hierarchy Process (AHP). A quantitative descriptive–analytical approach was employed, focusing on a restaurant enterprise in Bandung, Indonesia, operating a centralized supply chain system with 105 outlets. Expert judgments were collected through AHP questionnaires, supported by interviews and focus group discussions. The SCOR framework was used to structure supply chain processes, while AHP was applied to determine the priority weights of halal traceability criteria and sub-criteria. Consistency of judgments was ensured using the Consistency Ratio threshold of 0.10. The results indicate that the Fulfill process is the most critical stage in ensuring halal traceability, followed by Source and Transform, while Plan and Order play supporting roles. At the sub-criteria level, halal integrity during delivery emerged as the most critical factor, highlighting the vulnerability of downstream logistics to halal non-compliance. The integration of SCOR and AHP enabled the development of a priority-based strategic framework that aligns process importance with performance metrics and improvement actions. This study contributes to halal supply chain management literature by transforming SCOR from a descriptive process model into a prescriptive decision-support framework. From a practical perspective, the proposed SCOR–AHP framework provides actionable guidance for prioritizing resources, strengthening halal logistics governance, and enhancing the effectiveness, efficiency, and sustainability of halal traceability systems in the food industry